Effects of Decline in Fish Landings on the Livelihoods of Coastal Communities in Central Region of Ghana. Issue 6 (2nd November 2021) - Danquah, Jones Abrefa; Roberts, Charity Odumale; Appiah, Mark
Abstract: Fishing along Ghana's coast is the main livelihood for local communities, and it contributes significantly to their incomes. Most of them get employment, food security, and access to better health care through fishing activities. However, the fishing industry has been saddled with many challenges in recent times, which has led to low landings. This study aimed to assess the causes and effects of the decline in fish landings on the livelihood of coastal communities in the Central Region of Ghana. The systematic sampling technique was used to randomly select 200 households from four communities. A questionnaire was designed to elicit information from fisherfolk based on Likert scale estimation. In addition, time-series data of fish landings and imports for 51 years (1976–2017) was used in the analysis. The results from the study indicate that fish landings are declining, and this is affecting the income levels of fisherfolk. However, the impact of income decline on the female fisherfolk is lower as compared to their male counterparts. To mitigate against dwindling incomes, the fisherfolk have adopted livelihood diversification coping strategies. The key livelihood options identified in the communities are masonry, trading, and commercial driving. The fisherfolk mentioned overfishing, pollution, use of smaller mesh size nets, and unapproved methods of fishing as drivers of decline in fish landings. This study recommends that mandated institutions with oversight responsibilities in the fishing industry should be strengthened to enable them to conduct their functions effectively, so, they halt the decline in fish catch.